Vulnerability and Resilience Among Senior Citizen Street Vendors in the City of Koronadal, Philippines Amidst COVID-19 Pandemic - Francis Elian Marc L. Hutba; Charlene June L. Diezon; Dr. Jun Y. Badie (International Journal of Social Sciences: Current and Future Research Trends, 2023)
With the changes in the environment, especially during the COVID-19 pandemic, it was perceived that senior citizen street vendors are considered one of the vulnerable groups who are affected by unexpected social change. This study examined the vulnerability and resilience among senior citizen street vendors through a qualitative descriptive research method and conducted an in-depth interview with five participants who were qualified for the criteria that were set by the researchers. The study was conducted in the City of Koronadal. The researchers examined the data extracted from the participants through a thematic analysis of their experiences of vulnerability, resilience, challenges, and coping mechanisms. Based on the study, it was found out that senior citizen street vendors experienced overarching challenges because of their vulnerability to the loss of their income and to economic risks, which were crucial to their livelihood and survival, but with innate resilience, namely their persistence, adaptability, flexibility, and will to survive, they could continue street vending amidst the pandemic. These vendors also faced challenges in terms of the social exclusion of older persons, and the unsustainability of the livelihoods that they encountered, but they were able to lessen the effects of these challenges by employing coping mechanisms such as acceptance and open-mindedness. A conceptual model that would visualize the vulnerability, resilience, challenges, and coping mechanisms were created to present the realities of the senior citizen street vendor in the City of Koronadal